The Influence Of Work Environment And Individual Characteristics On Employee Performance At Pt. Sarana Bengkulu Ventura - Intihan Intihan; Defi Triansyah; Evita Sari; Leo Tarnando; Tyara Anggelya Putri (Journal of Research in Social Science and Humanities, 2025)
This This research was carried out at PT. Sarana Bengkulu Ventura. The formulation of the research problem is 1) Does the work environment influence the performance of PT. Sarana Bengkulu Ventura? 2) Do individual characteristics influence PT. Sarana Bengkulu Ventura? 3) Do the environment and individual characteristics influence the performance of PT. Sarana Bengkulu Ventura. The objectives of this research are 1) To determine the influence of the work environment on employee performance at PT. Sarana Bengkulu Ventura. 2) To determine the influence of individual characteristics on employee performance at PT. Sarana Bengkulu Ventura. 3) To determine the influence of the work environment and individual characteristics on employee performance at PT. Sarana Bengkulu Ventura. The population of this research is all employees of PT. Sarana Bengkulu Ventura as many as 25 people. This research sample used a total sampling method of 25 people. The data analysis used is multiple linear regression analysis, Determinant Coefficient, Hypothesis Testing with f-test and t-test. The results of the research are: 1) From the calculation of the multiple linear regression equation, it can be seen that the Work Environment (X1) and Individual Characteristics (X2) influence employee performance at PT. Sarana Bengkulu Ventura. Work environment coefficient (b) = 0.471 means that the work environment has a positive influence on employee performance or in other words, if the work environment increases 1 time, it will be followed by an increase in employee performance of 0.471. Individual characteristics coefficient (b) = 0.336 means that individual characteristics have a positive influence on employee performance or in other words, if individual characteristics increase 1 time, this will be followed by an increase in employee performance of 0.336. 2) The determinant coefficient (R2) value was 0.658. This value means that the work environment and individual characteristics contribute to employee performance by 0.658 or 65.8% and the remaining 34.2% is not studied in this research. 3) With the f-test, the hypothesis can also be proven to be true, where the work environment variables (X1) and individual characteristics (X2) show a p-value = 0.00 0.05 so that H0 is rejected and H1 is accepted. With the t test, the hypothesis was also proven to be true, where the work environment variable showed a calculated t value = 2.478 t table 2.060 so it was concluded that Ha was accepted. The individual characteristic variable shows the calculated t value = 2.680 t table 2.060 so it can be concluded that Ha is accepted.